Assessing the Implementation of Social Security Program for Tobacco Farmers in Jember Regency - Kardio, Bana; Susilo, Achmadi; Wisnujati, Nugrahini Susantinah (PT. Sangadji Media Publishing, 2024)
This research delves into the implementation of social security programs, particularly focusing on tobacco farm workers in Jember regency, Indonesia. Despite the mandatory nature of the BPJS Ketenagakerjaan, many tobacco farm laborers remain uncovered, posing risks to their social and economic well-being. Utilizing a quantitative research methodology, the study employs questionnaires and statistical analysis to understand the factors influencing participation in the BPJS Employment program. Findings reveal that variables such as Program Urgency, Farmers' Knowledge, Program Benefits, Farmers' Expectations, and the Role of Local Government collectively explain 67.5% of tobacco farmers' participation. Notably, Program Urgency and Program Benefits significantly impact participation, highlighting the vital role of social security in providing financial assurance against job-related risks. Moreover, active involvement of the Local Government is essential in fostering farmers' interest and engagement in the program. These findings underscore the significance of social security programs for tobacco farm workers, emphasizing the need for government support and facilitation to enhance program participation and ensure the welfare of vulnerable laborers.